PENGARUH EDUKASI GIZI MELALUI KOMIK DAN LEAFLET TERHADAP PENINGKATAN PENGETAHUAN TERKAIT ANEMIA PADA REMAJA PUTRI DI SMA NEGERI 14 JAKARTA - HERDARA HANNANTI (2020)
Background : Anemia is still a major public health problem in the world. Indonesia become one of the countries experiencing triple burden of malnutrition and one of them is anemia. The current situation of covid-19 pandemic considered worsen the challenge. Education especially about anemia problem on adolescents girl play an important role in the emergency response covid-19 pandemic. Objective : To determine the effect of nutrition education using comic and leaflet on the improvement of anemia knowledge in adolescents girl in SMA Negeri 14 Jakarta . Method : Quasy experimental study with pre-post test group design involving 126 female students in class X and XI which choosed by cluster random sampling. Knowledge data collected with online method. Result : The result was there were differences in respondents knowledge on the effect of nutrition education using comic (p=0,000) and leaflet (p=0,000) media. Conclusion : There is an effect of nutrition education using comic and leaflet on anemia knowledge in adolescents girl in SMA Negeri 14 Jakarta.